2013
DOI: 10.1007/s11051-013-2130-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the physicochemical properties of titanium dioxide nanoparticles, commonly used as sun protection agents, on microvascular endothelial cells

Abstract: Until now, the potential effects of titanium dioxide (TiO2) nanoparticles on endothelial cells are not well understood, despite their already wide usage. Therefore, the present work characterizes six TiO2 nanoparticle samples in the size range of 19 × 17 to 87 × 13 nm, which are commonly present in sun protection agents with respect to their physicochemical properties (size, shape, ζ-potential, agglomeration, sedimentation, surface coating, and surface area), their interactions with serum proteins and biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…TiO2 NPs had the power to influence the metabolic activity of human microvascular endothelial cells (ECs). 36 Pulmonary exposure of rats to TiO2 NPs increased the cardiac protein phosphorylation which may have involved a lung-neuron-regulated pathway, such as substance P synthesis in the nodose ganglia. 37 By investigating the interaction between TiO 2 NPs and the vascular system (primary vascular EC), Han et al 38 found that following exposure to NPs, the levels of monocyte chemoattractant protein-1 (MCP-1) and VCAM-1 were increased and the DNA binding activity of nuclear factor (NF)-jB was significantly elevated, which are characteristics of endothelial inflammation.…”
Section: Bio-toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…TiO2 NPs had the power to influence the metabolic activity of human microvascular endothelial cells (ECs). 36 Pulmonary exposure of rats to TiO2 NPs increased the cardiac protein phosphorylation which may have involved a lung-neuron-regulated pathway, such as substance P synthesis in the nodose ganglia. 37 By investigating the interaction between TiO 2 NPs and the vascular system (primary vascular EC), Han et al 38 found that following exposure to NPs, the levels of monocyte chemoattractant protein-1 (MCP-1) and VCAM-1 were increased and the DNA binding activity of nuclear factor (NF)-jB was significantly elevated, which are characteristics of endothelial inflammation.…”
Section: Bio-toxicitymentioning
confidence: 99%
“…Mallik et al reported that the considerable increase in OS and substantial decrease in the mitochondrial membrane potential (ΔΨm) in rat cardiac (H9c2) cells were caused by platinum‐modified TiO2 NPs (Pt‐TiO2 NPs), indicating that the Pt modification of the NPs rendered them more cytotoxic than the unmodified NPs. TiO2 NPs had the power to influence the metabolic activity of human microvascular endothelial cells (ECs) . Pulmonary exposure of rats to TiO2 NPs increased the cardiac protein phosphorylation which may have involved a lung‐neuron‐regulated pathway, such as substance P synthesis in the nodose ganglia …”
Section: Bio‐toxicitymentioning
confidence: 99%
“…This review article concentrates on synthesis and characterization of fluorescent silica and ceria NP, the latter also decorated with noble metals as models for decomposition products of automobile catalysts. We have recently reported on fluorescence-labelled coated titania NP and their interaction with human cell lines [ 1 ] and pointed out that the determination of the biological effects of zinc oxide NP is problematic since they are sensitive towards phosphate ions [ 2 ]. This work will not be included in this article.…”
Section: Reviewmentioning
confidence: 99%
“…The most striking behavior of nanoscale particle size of NM is observed on its ability to penetrate physiological barriers, which are merely impenetrable to their larger counterparts. Smaller size of NM facilitates their movement across epithelial/endothelial cells and cellular uptake . Due the same feature NM may move to other body parts and can get accumulated which prolong their stay in different tissues.…”
Section: Introductionmentioning
confidence: 99%